A Memory Structure with Different Control Gates. (17th May 2018) - Dai, Mingzhi; Guan, Jianmin; Song, Zhitang
Abstract: Memory is a key and fundamental component in integrated circuits (IC). A dominant volatile memory is the dynamic random access memory (DRAM) with one transistor and one capacitor, whose footprint is comparable to about two transistors. Memory structure needs further simplification according to IC's scaling‐down requirement. However, most updated structures at present are still mainly limited in lab. Here, a memory structure with one transistor is demonstrated. The advantages of this new structure over conventional memory structures include the simplification of the structure by saving a capacitor space in DRAM, and thus the simplification of fabrication process. Typical characterization of the memory device is also performed, and very quick response time (≈1 ns), which is faster than most present memories in the foundry, that is, 2 ns or more, is reported. Both simulation and experiments are performed to explain the memory working mechanism. The memory programming functions are implemented through the junction caused by control gate. This structure could be scaled down by using lithography processes in the foundry, which could ensure a fair reliability and enable immediate applications for information technology electronics as a potential alternative candidate for DRAM. Abstract : Updated memory structures are of importance for the development of integrated circuits. Here, a memory having only one transistor is proposed to replace dynamic random access memory (DRAM), having one transistor and one capacitor. The memory is faster (≈1 ns) than most present memories (>2 ns), and compatible with modern foundry lithography process which facilitates scaling‐down. This compact structure may enhance further memory development.